Dental education during the pandemic: Cross‐sectional evaluation of four different teaching concepts. Issue 10 (27th May 2021) - Goob, Janosch; Erdelt, Kurt; Güth, Jan‐Frederik; Liebermann, Anja
Abstract: Objectives: To evaluate the advantages of student satisfaction with and functionality of three digital teaching concepts during the SARS‐CoV‐2 pandemic compared to a conventional lecture setup. Methods: This cross‐sectional study was a survey‐based e‐learning research among dental students in the clinical study phase of a department of prosthetic dentistry at a German university hospital. A total of 44 questions were answered in four main sections: 1. general technical components; 2. acceptance; 3. evaluation and functionality; and 4. overall evaluation and grades of the various digital concepts. The use of Zoom conference, livestream, and prerecorded PowerPoint was compared to the conventional lecture setup (control group/CG). Data were analyzed using the Kolmogorov‐Smirnov test, followed by an exploratory data analysis and Cronbach's alpha test ( α  = 0.05). Results: Students were very satisfied with the provision, quality, and benefit of the digital concepts. The asynchronous concept was significantly more satisfying than the synchronous concepts in many aspects but was less successful in interactions. In the overall evaluation and grading, the asynchronous concept was rated significantly better than the other synchronous concepts ( p  ≤ 0.007), followed by Zoom conference, conventional lecture (CG), and livestream, while Zoom conference and the conventional lecture showed no significant difference ( p  = 0.784). Conclusions: Students significantly preferred the asynchronous concept to the synchronous concepts. The results suggested that asynchronous concepts are an effective and functional form of distance education during a pandemic. In general, digital teaching concepts are currently widely accepted for maintaining university education.